Inertia in Routines: A Hidden Source of Organizational Variation - Yi, Sangyoon; Knudsen, Thorbjørn; Becker, Markus C. (Organization Science, 2016)
Traditionally, routines have been perceived as a primary source of inertia, which slows down organizational change and hinders organizational adaptation. Advancing prior research on routine dynamics, this study examines how inertia in routines influences the process of organizational adaptation, both in the absence and presence of endogenous change of routines. Contrary to conventional wisdom, our analysis suggests an overlooked mechanism by which routine-level inertia may help, rather than hinder, organization-level adaptation. We demonstrate this mechanism by using a simple theoretical model in which the organization is characterized as a configuration of interdependent routines and study the process by which this configuration adapts to cope with its task environment. We find that inertia in routines may engender potentially useful variation in the process of organizational adaptation because reduced rates of routine-level changes may lead to temporal reordering when these changes are implemented. In our nuanced perspective, inertia is not only a consequence of adaptation or selection as perceived in prior research, but also a source of variation that turns out to be useful for adaptation. This logic is helpful to better understand why apparently inertial organizations keep surviving and from time to time exhibit outstanding performance. We conclude by discussing how this advanced understanding of the role of routines in organizational adaptation helps elaborate the theory of economic evolution.